2005
DOI: 10.1007/s00127-005-0947-x
|View full text |Cite
|
Sign up to set email alerts
|

Subjective quality of life of family caregivers of community living Sudanese psychiatric patients

Abstract: Caregivers who are women, parents, and sick seemed relatively vulnerable and need assistance. Their areas of dissatisfaction with material circumstances should be addressed in a social welfare program. Caregivers' inner strengths, extended family supports, and positive appreciation of the patients are resources for enhancing their caregiving role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 36 publications
6
44
0
2
Order By: Relevance
“…Parents had a statistically significant (p=0.009) poorer Quality of Life when compared to caregivers in other relationships (children, sibling). Similarly, Aschbrenner KA et al [18] found parents to have a very high degree of burden and Awadalla AW et al [19] found parents to have least QOL scores.…”
Section: Discussionmentioning
confidence: 95%
“…Parents had a statistically significant (p=0.009) poorer Quality of Life when compared to caregivers in other relationships (children, sibling). Similarly, Aschbrenner KA et al [18] found parents to have a very high degree of burden and Awadalla AW et al [19] found parents to have least QOL scores.…”
Section: Discussionmentioning
confidence: 95%
“…Severe positive symptoms of schizophrenia such as hallucination, delusion, aggressiveness and destructive behavior are known to cause distress to the caregivers and lower their QOL (10,12). It is suggested that the threatening nature of positive symptoms even though they are more episodic, as compared to the less threatening negative symptoms even though they are more chronic, make them more intolerable to caregivers (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…Higher educational level appears to provide an advantage to the caregivers. It is speculated that better knowledge give rise to better capability to cope with their caregiving task as well as other stressors in life (10,43). Caregivers with higher education possibly have more secured job and stable financial income that reduce the financial burden on caregiving task, thus improving their satisfaction for lives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Una posible explicación de la diferencia con los resultados de este estudio es la independencia del paciente según perfil PULSES, y que cerca de la mitad de los cuidadores están dedicados al hogar y dependen de sus propios ingresos (33). Si bien el aislamiento es "la soledad que se experimenta como negativa, amenazadora e impuesta por otros" (34), y aún no es manifestada por los cuidadores del estudio, se debe evitar su aparición mediante estrategias dirigidas a los cuidadores que asisten con la persona en situación de cronicidad a los programas de promoción y prevención, como disfrutar el tiempo libre y reunirse con sus familiares para satisfacer las necesidades sociales y promover su calidad de vida (35).…”
Section: Bienestar Socialunclassified